Organisation management in the digital economy: graduation according to the degree of using digital technologies - A. V. Veretyokhin (Вестник университета)
The active introduction of   digital technologies by   business entities does not only rapidly change their external and internal environments, but also affects the essence of   the economy, forming qualitative structural transformations in   it, which should be   reflected in   the terminology. The purposes of   the work are to  analyse modern approaches to   the interpretation of   the digital economy; to   consider the conceptual and terminological situation in   the management of   an organisation; to   propose a   reasonable terminological set of   concepts reflecting the gradation of   management according to  the degree of   digital technologies application. The author has conducted the research within the framework of a   systematic information and cybernetic scientific approach. Scientific methods, such as  analysis, synthesis, generalisation, comparison, etc., are used. The data is  taken from open sources. The author has analysed and summarised approaches to  the interpretation of  the digital economy, has grouped them and allocated as   follows: technocratic, specific, scientific and industrial, industrial and sectoral, information and spatial, evolutionary. The article uses the generic concept “digital economy” and reasonably suggests a   set of   terms, such as   “analog management”, “digitised management”, and “digital management” to  differentiate the concept “organisation management” according to   the degree of   applying digital technologies. The paper shows the expediency of   this gradation (including semantic content and terminological continuity), its integrity, completeness, consistency, and compliance with modern scientific knowledge. The author suggests using the introduced set of  terms for various socio-economic phenomena, processes, and objects.